PERHITUNGAN PEMBIAYAAN DANA PENSIUN DENGAN METODE ATTAINED AGE NORMAL DAN PROJECTED UNIT CREDIT (STUDI KASUS : PT. TASPEN (PERSERO) KANTOR CABANG UTAMA SEMARANG) - Musandingmi Elok Nurul Islam; Yuciana Wilandari; Suparti Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Welfare in the future is something that all people dreamed, including goverment employees. As a government's concern for welfare in the future for the goverment employees so the government give pension program. The pension program will give pension benefit to the goverment employees on their retirement age. Pension funding requires actuarial computation which normal cost and actuarial liability. Actuarial computation is divided into two major parts, Accrued Benefit Cost Method and Projected Benefit Cost Method. One of Accrued Benefit Cost Method example is Projected Unit Credit and for the Projected Benefit cost one of the method is Attained Age Normal. This research uses secondary data from PT. TASPEN (Persero) KCU Semarang. Computation result shows on the both second normal cost the method tends to increase each year. Projected Unit Credit Method exhibits substansial increment, meanwhile on Attained Age Nornal Method the increment is relatively slow. The amount of both second actuarial liability method will always increase each year, by using Attained Age Normal Cost produces bigger actuarial liability than Projected Unit Credit Method. Projected Unit Credit Method give final normal cost less than Attained Age Nornal Method. Keywords: Pension, Normal Cost, Actuarial liability, Attained Age Normal, Projected Unit Credit.